Increased Expression of Transthyretin in Leptin‐Deficient ob/ob Mice is not Causative for Their Major Phenotypic Abnormalities. (21st December 2012) - Rendenbach, C.; Ganswindt, S.; Seitz, S.; Barvencik, F.; Huebner, A. K.; Baranowsky, A.; Streichert, T.; Niemeier, A.; Heeren, J.; Amling, M.; Bartelt, A.; Schinke, T.
<x xml:space="preserve">Abstract</x> The hormone leptin is a critical regulator of adipogenesis and energy metabolism. Similarly, leptin‐deficient ob/ob mice display various metabolic abnormalities, including not only obesity and insulin resistance, but also hypogonadism and high bone mass. By genome‐wide expression analysis using hypothalamus RNA from wild‐type and ob/ob mice, we observed the increased expression of the gene for transthyretin (Ttr) in the latter, as confirmed by quantitative real‐time‐polymerase chain reaction. Because Ttr encodes a carrier protein for retinol transport, and because we further found increased retinol levels in the serum of ob/ob mice, we investigated whether the additional absence of Ttr would influence the ob/ob phenotype. It was found that Ttr‐deficient ob/ob mice were indistinguishable from ob/ob littermates in terms of body weight, as well as serum glucose, insulin and cholesterol levels. Although all of these parameters were identical to wild‐type controls in Ttr‐deficient mice, we found that the sole deletion of Ttr caused a significant increase of trabecular bone mass, bone marrow adiposity and mean adipocyte area in white adipose tissue. Interestingly, all these latter parameters were highest in Ttr‐deficient ob/ob mice, and only in these mice did we observe a full penetrance of liver steatosis at 24 weeks of age. Taken together, our data demonstrate that the increased expression of Ttr in ob/ob mice does not cause (but rather attenuates) their phenotypic abnormalities.